2022
DOI: 10.3389/fmed.2022.944909
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical characteristics between SARS-CoV-2 Omicron variant and Delta variant infections in China

Abstract: BackgroundThe continued ‘evolution’ of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to the emergence of the Omicron variant after the Delta variant, resulting in a significant increase in the number of people with COVID-19. This increase in the number of cases continues to have a significant impact on lives. Therefore, a more detailed understanding of the clinical characteristics of Omicron infection is essential.MethodsUsing medical charts, we extracted clinical information for 384 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Among the patients admitted to ICU, 73% had hypertension and 49% diabetes in Delta, while 69% had hypertension and 62% diabetes in Omicron wave. There have been studies showing a comparison of clinical characteristics between the Delta variant and the Omicron variant of SARS-COV-2 infections [13] however not much research has been done comparing the CBC parameters and emphasizing its relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Among the patients admitted to ICU, 73% had hypertension and 49% diabetes in Delta, while 69% had hypertension and 62% diabetes in Omicron wave. There have been studies showing a comparison of clinical characteristics between the Delta variant and the Omicron variant of SARS-COV-2 infections [13] however not much research has been done comparing the CBC parameters and emphasizing its relevance.…”
Section: Discussionmentioning
confidence: 99%
“…2). Twenty-two studies were from populations primarily of European ancestry [8,32,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], eight studies on East Asians [60][61][62][63][64][65][66][67], three studies on South Asians [68][69][70], three studies on Latinos [71][72][73], four studies on populations in Africa [74][75][76][77], and one study from West Asia (Turkey [78]). The location of studies, with the prevalence indicated by the color intensity, and the cohort size indicated by the size of the circles, shows that Western countries report the highest prevalence, while studies from East Asia and Africa report the lowest prevalence (Fig.…”
Section: Properties Of Studiesmentioning
confidence: 99%
“…2). Twenty-five studies were from populations primarily of European ancestry [9,30,, seventeen studies on East Asians [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] (note that one of these studies, [75], reports on the same cohort as [74], and therefore was removed from the meta-analysis), eight studies on South Asians [79][80][81][82][83][84][85][86], four studies on Latinos/Hispanics [87][88][89][90], five studies on populations in Africa [91][92][93][94][95], and three studies from the Middle East [96][97][98]. The location of studies, with the prevalence indicated by the color intensity, and the cohort size indicated by the size of the circles, shows that Western countries report the highest prevalence, while studies from East Asia and the Middle East report the lowest prevalence (Fig.…”
Section: Properties Of Studiesmentioning
confidence: 99%
“…In China, the prevalence of olfactory dysfunction caused by the Omicron variant is 0-9% (Li et al 2022;Liang et al 2022;Yang et al 2022;Zhang et al 2022;. However, the sample size is relatively small and the researchers focus on the characteristics and clinical symptoms with insufficient discussion on chemosensory changes.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the prevalence of olfactory dysfunction caused by the Omicron variant is 0-9% (Li et al 2022; Liang et al 2022; Yang et al 2022; Zhang et al 2022; Shen et al 2022). However, the sample size is relatively small and the researchers focus on the characteristics and clinical symptoms with insufficient discussion on chemosensory changes.…”
Section: Introductionmentioning
confidence: 99%